An evaluation for the standardization of the Allium cepa test as cytotoxicity and genotoxicity assay. Issue 3 (3rd July 2018) - Bonciu, Elena; Firbas, Peter; Fontanetti, Carmem S.; Wusheng, Jiang; Karaismailoğlu, Mehmet Cengiz; Liu, Donghua; Menicucci, Felicia; Pesnya, Dmitry S.; Popescu, Aurel; Romanovsky, Anton V.; Schiff, Silvia; Ślusarczyk, Joanna; et al.
ABSTRACT: A general report on the use of the Allium test as cytotoxicological and genotoxicological assay is proposed, with particular emphasis about the standardization of the test in several common applications. The intraspecific variation in Allium cepa has been overlooked, as in most investigations no mention is made about origin and denomination of the onion cultivar used. A standardization of the used material would allow a better generalization of the results, since we cannot be sure that all cultivars would give the same response. A more frequent use of transmission electron microscopy (TEM) investigation is proposed. Even if relatively time consuming and not available in all laboratories, it may help to better understand the mechanism of cytotoxicity, since many morphological characters may appear similar but be arisen from different processes observable only with TEM. About statistical testing, tests other than chi-squared may be used in case of a lower amount of data. The most commonly used statistical tests are the parametric tests ANOVA and Student's t, and the non-parametric tests Kruskal–Wallis and Mann–Whitney U, for analysis of variance. Tests should be used also to assess the minimal sample dimension for obtaining significance, since data collection (microscope observation) appears to be one of the main bottle necks of the test. Also the use of the Allium test for testing liposomes and other nanovectors for drug delivery is proposed, in order to assess the cytotoxicity of these types of medium and the possible increase in cytotoxicity of the associated drug.